Self-regulation training improves stress resilience in elite pre-pubescent female gymnasts - Proietti, Giorgia; Borozan, Milos; Chaigneau, Amine; Cannito, Loreta; Palumbo, Riccardo; Thouvarecq, Regis; Iodice, Pierpaolo (Frontiers in Psychology, 2024)
In the context of young female athletes, especially namely elite gymnasts, effective stress management strategies not only enhance performance, but also reduce the risk of injuries and promote overall well-being. This study aims to investigate the effects of biofeedback-based training on stress management in prepubescent elite female gymnasts, recognizing its pivotal role in promoting healthy growth and proper training load management.Eight elite young female athletes from a top flight French national league club participated in an experimental condition involving four-week biofeedback training program to improve selfregulation skills, during both rest and stress phases. Additionally, each subject experienced a control condition, with entailed exposure to domain-specific motivational videos.Comprehensive evaluations of physiological parameters were conducted to assess the impact of biofeedback training, both before and after the training, as well as during the stress and recovery phases. Furthermore, an interoceptive body awareness test, using the MAIA questionnaire, was performed.The results highlight a significant enhancement in of the self-regulatory skills of the gymnasts to manage in managing the selected physiological parameters -peripheral temperature (p < 0.05) and blood volume pressure (p < 0.05) -after the biofeedback treatment. Moreover, psychological data from the MAIA questionnaire revealed a noteworthy increase in interoceptive awareness (p < 0.001), particularly in the subscales of Not Distracting (p < 0.001), Attention regulation (p < 0.05), Emotional awareness (p < 0.05), and Self-regulation (p < 0.05).Biofeedback Thus, we conclude that biofeedback training enables the improves self-regulatory ability abilities and psychological resilience under stressful conditions, while reducing sensitivity to gymnastics-specific stress.